Erratum: Aromaticity and sterics control whether a cationic olefin radical is resistant to disproportionation (Chem. Sci. (2020) 11 (4138-4149) DOI: 10.1039/D0SC00699H) - Messelberger, Julian; Grünwald, Annette; Goodner, Stephen; Zeilinger, Florian; Pinter, Piermaria; Miehlich, Matthias; Heinemann, Frank Wilhelm; Hansmann, Max M.; Munz, Dominik (Chemical Science, 2021)
The authors regret that funding details were incorrect in the acknowledgements section of the original article. The corrected acknowledgements section for this article is shown below.
CRIS-Team Scopus Importer:2021-07-16